LOW-FIELD VARIATION OF MAGNETIC SUSCEPTIBILITY AND ITS EFFECT ON THE ANISOTROPY OF MAGNETIC SUSCEPTIBILITY OF ROCKS - Hrouda F. (My University, 2002)
The theory of the low-field anisotropy of magnetic susceptibility (AMS) assumes a linear relationship between magnetization and the magnetizing field. This assumption is precisely valid in diamagnetic and paramagnetic minerals by definition, while in ferrimagnetic and antiferromagnetic minerals this relationship is in general non-linear (represented by a hysteresis loop), being linear only with very weak fields in which the initial susceptibility is measured. Recently, it has been shown that, in using common measuring fields, the field-independent susceptibility is measured in magnetite, while in pyrrhotite, haematite and titanomagnetite it may often be outside the initial susceptibility range. The problem can be solved in three ways. The simplest way is using very weak measuring fields (less than 10 A m-1 ), but this can result in significant lowering of sensitivity and precision. The second way is to respect the non-linearity and measure the susceptibility in so many directions that contour diagram of directional susceptibilities can be presented instead of a susceptibility ellipsoid. The third way is to measure the AMS within the Rayleigh law range and calculate the initial directional susceptibilities from which the AMS can be correctly determined using linear theory.
Keywords: ANISOTROPY; FIELD VARIATION; MAGNETIC SUSCEPTIBILITY